English and American studies in German. (Tibungen : Max Niemeyer Verlag, 1969)
"Summaries of theses and monographs."
Max Niemeyer Verlag
Keywords: English philology -- Abstracts -- Periodicals; American literature -- Abstracts -- Periodicals; Dissertations, Academic -- Germany -- Abstracts -- Periodicals